Potensi Pemanfaatan Limbah Endapan Asam Fosfat dan Limbah Kapur ZA II sebagai Bahan Baku Pembuatan Pupuk SP – 15 - Fawwaz Akhdan Praditya; Rizka Novembrianto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study explores the potential utilization of phosphoric acid sludge and ZA II lime waste as raw materials for the production of SP-15 fertilizer, which is essential for enhancing agricultural productivity and addressing environmental issues related to waste disposal. The research aims to analyze the phosphorus content (P₂O₅), moisture levels, sulfur (S), and calcium oxide (CaO) in the raw materials and the final fertilizer product. Methods employed include sampling, gravimetric analysis, and spectrophotometry. The findings indicate that phosphoric acid sludge contains an average P₂O₅ content of 33.05%, making it a potential phosphorus source for fertilizer production. Additionally, ZA II lime demonstrates good hygroscopic properties. This research concludes that utilizing these two wastes can not only reduce reliance on chemical fertilizers but also provide economic benefits to farmers and support sustainable agriculture. The implications of this study highlight the need for further research to optimize waste processing techniques and enhance community awareness regarding waste management.